2010
DOI: 10.1007/s00468-010-0532-8
|View full text |Cite
|
Sign up to set email alerts
|

Aspen shoots are carbon autonomous during bud break

Abstract: Current thinking holds that carbon autonomy of branches in trees is unlikely, particularly during bud break, when the new developing shoots require significant influx of carbon resources from more distant sources. Results from recent studies indicate that the impact of bud break on overall tree reserves might be small. In two studies the independence of flushing shoots from stored carbon reserves and the photosynthesis in developing new leaves and shoots of Populus tremuloides were explored. New developing sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 34 publications
7
28
1
Order By: Relevance
“…As a result, the reflushing of leaves after a defoliation event might not be as costly as one would expect. In abscised aspen shoots, stored reserves were lowered only by 14% during budflush and with shoot reserves being rebuilt after only 7 days after the flush of new leaves (Landhäusser 2011). It appears that in seedlings and small trees, the bole is small and will behave more like a branch on a mature tree where sinks are smaller and C reserves can accumulate even during periods of stress (Ludovici et al 2002;Sanz-Pérez et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…As a result, the reflushing of leaves after a defoliation event might not be as costly as one would expect. In abscised aspen shoots, stored reserves were lowered only by 14% during budflush and with shoot reserves being rebuilt after only 7 days after the flush of new leaves (Landhäusser 2011). It appears that in seedlings and small trees, the bole is small and will behave more like a branch on a mature tree where sinks are smaller and C reserves can accumulate even during periods of stress (Ludovici et al 2002;Sanz-Pérez et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…). Recent studies have shown that deciduous temperate tree species use current photosynthates mostly for leaf formation, because developing leaves become C‐autonomous very soon after bud break (Keel & Schädel ; Landhäusser ). We can therefore use current leaves of deciduous tree species as an indicator of Δ 14 C of atmospheric CO 2 at the study site.…”
Section: Methodsmentioning
confidence: 99%
“…Upon outplanting, root TNC reserves are important for seedlings to survive the stressful environmental conditions, such as high water stress encountered immediately after planting (Grossnickle, 2005). New root growth in the closely related European aspen (Populus tremula) was dependent on current photosynthates (Eliasson, 1968) so adequate root TNC reserves could allow for early root growth in seedlings while stem reserves are adequate to support the flush of the new foliage in the spring (Landhäusser, 2011).…”
Section: Treatmentmentioning
confidence: 99%
“…These variables are currently being used for aspen and appear to be poor predictors for the quality of aspen planting stock. Stored carbohydrates reserves are important for the establishment and growth of seedlings, particularly in deciduous species that need to rely on the stored reserves to initiate leaf area and new root growth without current photosynthesis (Loescher et al, 1990;Turgeon, 1989;Chapin et al, 1990;Kozlowski, 1992;Kozlowski and Pallardy, 2002;Sprugel, 2002;Landhäusser, 2011).…”
Section: Introductionmentioning
confidence: 99%